Jefferson Davis, ex-president of the Confederate States of America : a memoir - Davis, Varina, 1826-1906 (New York : Belford Co., 1890)
This book examines Jefferson Davis's life as a United States statesman and President of the Confederacy.
Volume 1. Ancestry and boyhood -- Early education -- At Transylvania University -- Enters West Point -- West Point, 1818-25 -- Fort Crawford, 1825-29 -- Fort Winnebago, 1829-31 -- Yellow River, 1831 -- The Galena Lead Mines, 1831-32 -- Fort Frawford, 1832-33 -- The Black Hawk War -- Fort Gibson -- A Leington and Galena -- Fort Bibson, 1834 -- Return to Brierfield -- Hurricane and Brierfield, 1837-45 -- Begins his political life, 1843 -- Marriage 1845 -- In the twenty-ninth Congress, 1845-46 -- Visit of Calhoun, 1845 -- Mr. Davis's first session in Congress -- The secret service fund -- The Senate in 1845 -- Storming of Monterey, 1846 -- The Storming of Monterey -- After the battle of Monterey -- The in thirtieth Congress -- The Oregon question -- Cuban offers --Anti-slavery agitation -- Thirty-first Congress, 1849-50 -- Missouri Compromise -- From plantation to cabinet life -- First year in the cabinet -- Mr. Davis' second report -- Third year as secretary of war -- Fourth report -- Secretary of war, 1853-57 -- Cabinet life -- Social relations and incidents of cabinet life, 1853-57 -- The winter of 1859 -- Summer outing -- thirty-sixth Congress -- Charleston convention, 1860 -- Mr. Davis withdraws from the Senate.
Lib. Company. Afro-Americana
Mode of access: Internet.
Keywords: Davis, Jefferson, -- 1808-1889; Statesmen -- United States -- Biography; Statesmen -- Confederate States of America -- Biography; United States -- History -- Civil War, 1861-1865; Confederate States of America -- Politics and government; Confederate States of America -- History; History; Biographies